Michael Timothy Law, When God Spoke Greek. The Septuagint and the Making of the Christian Bible (Oxford – New York: Oxford University Press 2013) - Rambiert-Kwaśniewska, Anna Magdalena (The Biblical Annals, 2018)
Book review: Michael Timothy Law, When God Spoke Greek. The Septuagint and the Making of the Christian Bible (Oxford – New York: Oxford University Press 2013). Ss. 216. £20.99 ISBN 978-0-19-978172-0 DOI: https://doi.org/10.31743/ba.2018.8.3.07